Potensi Pengembangan Wisata Edukasi Berbasis Community Based Tourism di Desa Wisata Ngargoretno - Hanna Daniati; Lien Maulina; Dede Kuswandi; Siti Yulia Irani Nugraha; Eka Nuraisah Rosiana (STIEPAR YAPARI Bandung, 2022)
Community participation in a tourist village has a major influence on its development as a tourist attraction. The concept of Ngargoretno Village as an edutourism village requires the active role of the community in advancing and developing the existing natural and human potential, so that tourism activities in the village have a positive impact on the prosperity and progress of the village and society. The research was conducted using qualitative research methods, with data collection using structured interviews with tourism village managers, surrounding communities, village governments and tourists. The results showed that the Tourism Village of Ngargoretno can be categorized as educational tourism, because the attractions in the form of tourism and education at the tourist attraction of the Etawa Goat Farm and Manoreh Red Marble Hill have a high educational content. In addition to attractions in the form of edutourism, aspects of tourism products that are already good are accessibility and ancilieries services, while the amenity aspect, namely tourism supporting facilities, needs to be increased in quantity and pay attention to its condition. The Ngargoretno Village community plays an active role in the management and development of tourist villages. namely the community, forming and joining BUMDes POKDARWIS, as well as LPP. In developing the role of the community, training is also given in managing the tourism village business. The training was carried out in collaboration with the Borobudur Authority Agency (BOB), and Educational Institutions.